EARLY STAGES OF LIGNITE FORMATION IN PTOLEMAIS BASIN: A COAL-PETROGRAPHIC APPROACH - Siavalas, G.; Tsompanidou, E.; Kalaitzidis, S.; Bouzinos, A.; Christanis Κ. (Bulletin of the Geological Society of Greece, 2004)
With the present study it is intended to assess the depositional palaeoenvironment of the lower part of the Lignite-bearing Sequence in the Ptolemais Basin, and more specifically in the areas of Notio-Field and Tomeas-6 open pits. The sediments under study represent the seam between the Volcanic Tephra Layer and the Basal Marl, which constitute the roof and the floor, respectively. Coal-petrographic results showed that Huminite is the main macerai group (84-96%), while macérais from Liptinite and Inertinite groups display low values (<10%). In bulk lignite samples the main mineral phases are quartz, calcite, clay minerals and feldspars, while in the ashes the main phases are quartz, anhydrite and lime. The palaeoenvironment of the lignite formation was reconstructed using the lithological, coalpetrographic and mineralogical data, as well as coal-facies diagrammes. In Notio-Field Mine, at the early stages of lignite formation the conditions used to be limnotelmatic, while in Tomeas-6 Mine they were telmatic. Upwards the conditions turned to more telmatic in both mine areas. The vegetation was mainly herbaceous with some arboreal elements occurring mostly in Tomeas-6 area. The water influx was generally intense resulting in enhanced inorganic input